Defining the temperature range for cooking with extra virgin olive oil using Raman spectroscopy. (24th August 2017) - Ahmad, Naveed; Saleem, M; Ali, H; Bilal, M; Khan, Saranjam; Ullah, Rahat; Ahmed, M; Mahmood, S
Abstract: Using the potential of Raman spectroscopy, new findings regarding the effects of heating on extra virgin olive oil (EVOO) during frying/cooking are presented. A temperature range from 140 to 150 °C has been defined within which EVOO can be used for cooking/frying without much loss of its natural molecular composition. Raman spectra from the EVOO samples were recorded using an excitation laser at 785 nm in the range from 540 to 1800 cm −1 . Due to heating, prominent variations in intensity are observed at Raman bands from 540 to 770 cm −1, 790 to 1170 cm −1 and 1267 and 1302 cm −1 . The Raman bands at 1267 and 1302 cm −1 represent cis unsaturated fats and their ratio is used to investigate the effects of temperature on the molecular composition of EVOO. In addition, principal component analysis has been applied on all the groups of data to classify the heated EVOO samples at different temperatures and for different times. In addition, it has been found that use of EVOO for frying twice does not have any prominent effect on its molecular composition.